Perbandingan Analisis Kesalahan Antara Siswa Yang Menghafal Dan Tidak Menghafal Alqur’an Dalam Menyelesaikan Soal-Soal Cerita Pada Materi Program Linear Studi Kasus Di Madsarsah Aliyah Swasta Di Kabupaten Lombok Tengah - Mukminah Mukminah; Riana Riana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
Some mistakes that are often made by students in answering mathematical problems in the form of story problems are; factual errors, concept errors, principle errors, and operating errors. The purpose of this research is information in the field of education related to differences in mistakes of students who memorize and not memorize the Qur'an in solving word mathematical problems. The data sources are students of XI IPS MA private in central Lombok; six schools from three districts with memorize the Qur'an program. From each of these school 8-10 students will be taken to memorize and not memorize the Qur'an. This research was divided into 3 stages namely; initial, core and final stages. The results of this research indicate that the comparison of errors between students who memorize and not memorize the Qur'an in solving story questions on linear program material in 6 (Six) madsarsah aliyah private in Central Lombok shows that the average errors done namely fact errors.